The Improvement of Albanian Language Textbooks in the Primary School - Kraja, Pranvera (Richtmann Publishing, 2012)
This study aims to analyze and evaluate the fulfillment of the basic criteria and the complementary ones of the Albanianlanguage textbook 2 in Primary School and to show how it reflect the development and the demands of nowadays teaching science. Forthe realization of this study, are used a combination of research methods, including the analysis of text based on the normative criteria offormulation and evaluation of textbooks, interviews with language specialist and education inspector, the questionnaire with teachers andparents, focus groups with teachers. The results showed that the text of the Albanian language 2 is a good text, where scientific criteriaand contemporary didactics of teaching the mother-tongue at school are applied. As well, this new conception of text helps in going onintegrated culture to the pupils considering language as a universal communication mean, prompt in itself and in relation to othersubjects. The conclusions practically suggest the ways in which we can improve some aspects which have not been realized properly inorder to make better texts.